Disrupted cellular calcium homeostasis is responsible for Aβ‐induced learning and memory damage and lifespan shortening in a model of Aβ transgenic fly. Issue 8 (9th May 2022) - Cheng, Kuan‐Chung; Huang, Chih‐Yuan; Hsieh, Tsung‐Chi; Chiang, Hsueh‐Cheng
Abstract: Accumulated Aβ is one of the hallmarks of Alzheimer's disease. Although accumulated results from in vivo and in vitro studies have shown that accumulated Aβ causes learning and memory deficit, cell death, and lifespan reduction, the underlying mechanism remains elusive. In neurons, calcium dynamics is regulated by voltage‐gated calcium channel (VGCC) and endoplasmic reticulum and is important for neuron survival and formation of learning and memory. The current study employs in vivo genetics to reveal the role of calcium regulation systems in Aβ‐induced behavioral damage. Our data shows that although increased VGCC improves learning and memory in Aβ42 flies, reduction of VGCC and Inositol trisphosphate receptors extends Aβ42 flies' lifespan and improves cell viability. The complex role of calcium regulation systems in Aβ‐induced damage suggests that the imbalance of calcium dynamic is one of the main factors to trigger learning and memory deficit and cell death in the disease.